Binge-watching and gender-specific effects on academic, social, and mental well-being in children and adolescents - Nick Tse; Natalie Sze-Nga Pang; Xin Wang; Yiran Li; Camilla Kin-Ming Lo; Xue Yang (PLoS ONE, 2025)
Introduction Binge-watching refers to the consumption of screen-based content (excluding gaming) for five or more consecutive hours in a single session within the past month, which is an emerging behavior of concern among students. This study aims to examine the rate of binge-watching among children and adolescents in Hong Kong as well as the potential association with their psychological, social, and educational self-efficacy. Methods A cross-sectional survey was conducted with 2,267 students from primary and secondary schools in Hong Kong, recruited through convenience sampling. The survey assessed levels of binge-watching, mental health, sleep quality, social support, loneliness, and educational self-efficacy. Linear regression analyses were performed, both with and without adjustments for age and watching time by gender. Results The findings revealed that 47.1% of the participants (45.1% males and 49.3% females) engaged in binge-watching at least once in the past month. Binge-watching was positively associated with depression, anxiety, stress, and loneliness, but negatively associated with educational self-efficacy in both genders (p < .05). Gender-specific effects were found that binge-watching was significantly associated with poorer sleep quality in males (p < .001), but not in females (p > .05). In contrast, a significant negative association between binge-watching and social support was found in females (p < .01), but not in males. Conclusion This study emphasizes the significant rate of problematic watching patterns and various impacts. Early identification and early prevention are warranted.